Application of Multiple Linear Regression Models in Forming Priority patterns of Village Fund Budget Use - Nasution, Tia Alfi Sahara; Al-Khowarizmi (Yayasan Asmin Intelektual Berkah, 2024)
This study aims to analyze the factors that influence the level of utilization of the village fund budget in Dolok Maraja Village, Simalungun Regency. Descriptive quantitative method with Multiple Linear Regression analysis was used to achieve the objective. The results showed that there was a significant relationship between the independent variable (village fund budget) and the dependent variable (the utilization rate of the village fund budget). The factors that most influence the utilization rate of the village fund budget are population, area, and poverty level. Implication of The implication of this study is that the government should consider these factors in the process of allocating village fund budgets. Villages with larger populations, larger areas, and higher poverty rates require larger budget allocations to ensure effective and efficient village development. In addition, the importance of good governance of village fund budgets and active community participation in the process of planning and implementing village development is also highlighted in this study. Specifically, this study shows that every year, the utilization rate of the village fund budget increases by an average of 6.5632. Meanwhile, each increase in the number of poor people and the Village Fund Ceiling decreases and increases the utilization rate of the village fund budget by an average of 2.6104 and 3.7433, respectively. Village area did not have a significant effect. Although this regression model has low explanatory power, it is statistically valid and fits the observed data. This research highlights the importance for the government to consider the factors of population, area, and Village Fund Ceiling in allocating the village fund budget, as well as improving governance and community participation in village development.